Pemanfaatan Kulit Bawang Merah, Tangkai Cabai Rawit, dan Ampas Kopi Sebagai Bahan Utama Pupuk Organik Cair - Daniel Try; Juwita Situmeang; Dwi Aulia Syafira Purba; Qania Gultom; Ahd Aidil Fajri Lintang; Elfayetti Elfayetti; Elsa Kardiana (STKIP HARAPAN BIMA, 2026)
The increasing amount of household organic waste, such as onion peels, chili stems, and coffee grounds, requires effective management through its utilization as liquid organic fertilizer (LOF). This study aims to analyze the production process of liquid organic fertilizer and determine the nutrient content of nitrogen (N), phosphorus (P), and potassium (K) as indicators of fertilizer quality. This study employed an experimental method with a qualitative descriptive approach through an anaerobic fermentation process using EM4 and molasses for 10-14 days. The object of the study was liquid organic fertilizer produced from household organic waste, including onion peels, chili stems, and coffee grounds. Data were collected through direct observation during the fermentation process and laboratory testing of nutrient content. Data analysis was conducted descriptively through the interpretation of observational results and laboratory tests on nitrogen (N), phosphorus (P), and potassium (K) content. The results showed that the fermentation process proceeded optimally, indicated by a dark brown color change, a fresh acidic odor, and decomposed material texture. Laboratory test results revealed that potassium was the dominant nutrient compared to nitrogen and phosphorus. Although the nutrient content has not yet met national standards, the resulting liquid organic fertilizer has the potential to be used as an environmentally friendly supplementary fertilizer to support household organic waste management and sustainable agriculture.